Humanism and Calvinism Andrew Melville and the universities of Scotland, 1560-1625 - Reid, Steven J. (Farnham, England ; Burlington, Vt. : Ashgate, 2011)
This book surveys the transformation of Scotland's medieval and Catholic university system into a greatly-expanded Protestant one in the decades following the Scottish Reformation of 1560. It also assesses the contribution of religious reformer Andrew Mel.
Between Reformation and reform : the Scottish universities, 1560-74 -- Humanism and Calvinism : Melville's education, 1545-74 -- The first foray into reform : Melville and the "ancient" universities, 1574-84 -- Reform and reaction at St Andrews, 1579-88 -- The rise and fall of "Melvillian" St Andrews, 1588-97 -- The rise of "the moderates" in St Andrews, 1597-1606 -- "Godly" humanism, civic control : Scotland's Protestant arts colleges, 1582-c.1606 -- The Scottish universities post-Melville, c. 1606-25 -- Conclusion -- Appendix : student matriculations and graduations, 1559-1625.
Includes bibliographical references and index.
Print version record.
Keywords: Melville, Andrew, -- 1545-1622.; University of St. Andrews -- History; Melville, Andrew, -- 1545-1622.; University of St. Andrews -- History; Melville, Andrew, -- 1545-1622.; University of St. Andrews; Universities and colleges -- Scotland -- History -- 16th century; Universities and colleges -- Scotland -- History -- 17th century; Education, Higher -- Scotland -- History -- 16th century; Education, Higher -- Scotland -- History -- 17th century; Reformation -- Scotland; Scotland -- Intellectual life -- 16th century; Scotland -- Intellectual life -- 17th century; EDUCATION -- Higher; Education, Higher; Intellectual life; Reformation; Universities and colleges; Scotland; 1500-1699; Electronic books; History; Electronic books